Wayside School beneath the Cloud of Doom - Sachar, Louis, 1954- (New York, NY : Harper, 2020)
Follows the adventures and misadventures of students and staff as they cope with the effects of a large, gloomy cloud that has settled over Wayside School.
Ages 8-12.
Grades 4-6.
Keywords: Schools -- Fiction; Clouds -- Fiction; Humorous stories